Crossing the Ring: A Journey of the Nitroso-ene Reaction - Ouyang, Jie; Mi, Xianwei; Wang, Yan; Hong, Ran (Synlett, 2017)
Recent progress in the nitroso-ene reaction indicates the potentially rich reactivity of the nitroso species. In this study, we highlight the synthetic efforts towards the construction of the aza-spirocyclic or aza-bridged ring embedded in biologically significant alkaloids via the proposed approach. Our endeavors along this direction are exemplified in the formal synthesis of (±)-cephalotaxine and the total synthesis of (–)-hosieine A.1 Introduction2 Aza-Spirocyclane: A Formal Synthesis of (±)-Cephalotaxine3 Method Development4 Aza-Bridge Ring: A Total Synthesis of (–)-Hosieine A5 Epilogue
Keywords: alkaloids; alkene functionalization; mechanism; nitroso-ene reaction; total synthesis